Processuel strategi i organisationer: Monografi om dobbeltheden i tænkning af strategi, dels som vidensfelt i organisationsteori, dels som kunstnerisk tilgang til at skabe i erhvervsmæssig innovation - Martin Gylling (Copenhagen Business School (CBS), 2014)
This thesis is a study of processes of commercial artistic creation focusing on the practice of processual strategy in a context of designed strategy. The thesis focuses on the practice of processual strategy, seeing as strategy within the field is primarily understood and practised in a designerly approach. This concerns constructivist and objective thinking which, according to critical voices in organizationstudies, has difficulties explaining how strategic organisation creation gains a processual character. This is the critique that comes from the more poststructuralist positions in research on process theory and strategy, which in these years aims to move focus away from the dominance of designed strategy. I.e. an approach to practice understood as methodological individualism and pragmatic rationality (Chia & Holt 2009; Steyaert 2007; Stacey 2011; Hjorth 2012). Through recent poststructuralist currents in the field of processual strategy thinking and organisational entrepreneurship, for example Chia & Holt's creation philosophical research in strategy without design and Steyaert's (2007) thinking on the concept of entrepreneuring; the process theoretical thinking of entrepreneurship and innovation, the aim is to look beyond constructivist thinking of practice in order to understand processual dynamics in strategic work at the level of the organisation. In relation to this thinking the present thesis provides an empirically based discussion of processual strategy with an aim to contributing to the field of organisational entrepreneurship.
hdl:10398/8895
Keywords: 650